Mucosal healing of ileum-mucosa-associated lymphoid tissue lymphoma after Helicobacter pylori eradication: a case report and literature review - Huang, Yihan; Jiang, Jiaying; Jiang, Kui; Wang, Bangmao; Liu, Tianyu; Cao, Hailong (Frontiers in Oncology, 2025)
Mucosa-associated lymphoid tissue (MALT) lymphoma of the small intestine is relatively rare, and the treatment guideline has not been established yet. Here we present a case of MALT lymphoma in the terminal ileum, which regressed after Helicobacter pylori (H. pylori) eradication. A 53-year-old man had complained of abdominal discomfort and underwent a gastrointestinal endoscopic examination. H. pylori-associated erosive gastritis was diagnosed, and superficial ulcerated lesions were also found in the terminal ileum. Histopathologic examination and immunohistochemical analyses of ileal biopsy specimens confirmed the diagnosis of MALT lymphoma. No distant lymph node metastasis or other organ involvement was detected in positron emission tomography/computed tomography. Surprisingly, the ileum reached mucosal healing after quadruple therapy regimens for H. pylori eradication without additional treatments. There were no signs of recurrence during the follow-up for 18 months. The unique case which located only in the ileum revealed that eradication of H. pylori might be an effective treatment and deserves further studies. Moreover, we also provide a detailed overview of recently published literature regarding the eradication treatment for intestinal MALT lymphoma.